Cost-effectiveness of monitoring free flaps. Issue 5 (June 2016) - Subramaniam, Shiva; Sharp, David; Jardim, Christopher; Batstone, Martin D.
Abstract: Methods of free flap monitoring have become more sophisticated and expensive. This study aims to determine the cost of free flap monitoring and examine its cost effectiveness. We examined a group of patients who had had free flaps to the head and neck over a two-year period, and combined these results with costs obtained from business managers and staff. There were 132 free flaps with a success rate of 99%. The cost of monitoring was Aus $193/flap. Clinical monitoring during this time period cost Aus$25 476 and did not lead to the salvage of any free flaps. Cost equivalence is reached between monitoring and not monitoring only at a failure rate of 15.8%. This is to our knowledge the first study to calculate the cost of clinical monitoring of free flaps, and to examine its cost-effectiveness.